Maritime security as an essential condition of safety of life - Махмурова-Дишлюк, Олена Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In the article the problem of maritime security in terms of protection of human life. Served author’s definition of maritime security and risk in shipping. Outlines ways to improve the protection of life and health during transportation by water transport. Regulate the shipping refers to the priority areas of domestic policy. Creating legal incentives for the development of the transport system in accordance with the directions of the state enshrined in the Constitution of Ukraine, is one of the main keys to the welfare of society, its economic potential and protection of human life. That is why the implementation of effective control and supervision in the field of shipping, to ensure a high level of security, detection, suppression and elimination of violations of the law, should be given due attention by the State and its authorized bodies. Activity participants relations in transport should be legally regulated, since the use of vehicles may cause irreparable damage to life and health, environment, water world (animals, plants) and entail administrative or criminal liability of the members of such relations. Meanwhile, the legal regulation of navigation safety, means of river transport and small vessels still in its infancy. Numerous gaps and inconsistencies in the legal acts regulating control and surveillance of the safety of navigation in Ukraine does not allow to fully ensure an adequate level of protection of both human life and the environment. Only conduct, in our view, a unified state policy in maritime security, motivated and reliable legal framework and effective state control over its observance will ensure safe operation of sea and river transport as an important condition for the protection of human life.